An open-circuit fault-diagnosis method for inverters based on phase current. Issue 2 (4th June 2020) - Cheng, Shu; Zhao, Jundong; Chen, Chunyang; Li, Kaidi; Wu, Xun; Yu, Tianjian; Yu, Yongsheng
Abstract: The inverter is an indispensable part of a power electronics system. Its safety and stability are important indicators for evaluating the reliability of the system. Inverter faults are usually caused by operating faults in the switch elements. This paper therefore proposes a non-intrusive fault-diagnosis method for open-circuit faults in inverter semiconductor power switches. This method requires only a current signal. It is simple and economical. Faults can be diagnosed quickly using the proposed algorithm. First, the phase current waveforms before and after the open-circuit fault are analysed based on the mathematical model. Then, based on the analysis of the phase currents, the fault features are extracted and the fault is located using the proposed integration algorithm. Finally, the effectiveness and reliability of the proposed fault-diagnosis method are verified using a hardware-in-the-loop experiment.